Role and inhibition of GLI1 protein in cancer - Mastrangelo, Eloise (Lung Cancer (Auckl), 2018)
GLI1 is a transcriptional regulator involved in the development of different types of cancer. GLI1 transcriptional activity is regulated within the Hedgehog pathway (canonical activity), but can also be controlled independently (non-canonical activity) in the context of other signaling pathways. Experimental evidences show GLI1 involvement in both small- and non–small-cell lung cancers. Direct inhibition of the protein, in combination with other chemotherapeutic agents, represents a promising strategy for the treatment of different malignancies.